Discours féministe sur le génocide rwandais dans deux romans africains d’Afrique noire francophone : entre devoir de mémoire et écriture-femme - Didier Brou Anoh (Glad!)
There is growing evidence of the emergence of African feminism in novels. African writers have found a fertile space to express their feelings about topics like genocides. That of Rwanda in 1994 allows us to understand the words that divide and the dangers that lie in wait for our humanity. This study analyzes the feminist discourse on this tragedy. It shows how Véronique Tadjo in The shadow of Imana. Journey to the end of Rwanda and Monique Ilboudo in Murekatété, in a language of revolt, with raw words, present a revolutionary feminism.